Comparative analysis of postoperative curative effect of liver wedge resection and liver IVb + V segment resection in patients with T2b gallbladder cancer - Wang, Zichao; Liu, Hongliang; Huang, Yong; Wang, Jun; Li, Junjie; Liu, Lingpeng; Huang, Mingwen (Frontiers in Surgery, 2023)
To compare the therapeutic effects of wedge resection and liver segment Ⅳb + Ⅴ resection on patients with T2b gallbladder cancer.